SAT0539 TAFRO Syndrome: A Unique Mimicker of Systemic Lupus Erythematosus. (9th June 2015) - Fujita, K.; Shibuto, N.; Yamamura, Y.; Nomura, Y.; Momoki, N.; Ueno, A.; Nakao, K.; Maruyama, K.; Yamamura, M.
Abstract : Background: TAFRO syndrome has recently been reported as a Japanese variant of multicentric Castleman's Disease (CD), named due to the presence of thrombocytopenia, anasarca, fever, reticulin fibrosis of the bone marrow and organomegaly. The patients often showed hypergammaglobulinemia with autoantibody production, thus leading to a misdiagnosis of rheumatic diseases such as systemic lupus erythematosus (SLE). Methods: We here report three cases of TAFRO syndrome. Results: Case 1: A 65-year-old woman had fever, peripheral edema, purpura, proteinuria (>0.5 g/day), pericardial effusion, thrombopenia (41x10 3 /μL) and lymphadenopathy. Laboratory tests showed elevated C-reactive protein (CRP) at 5.12 mg/dL, hypoalbuminemia, and positivity of anti-nuclear antibody (ANA), rheumatoid factor (RF), lupus anticoagulant (LAC) and anti-SS-A antibody. Renal biopsy indicated minor abnormality with minimal immune complex deposition. The finding of lymph node biopsy was compatible with the hyaline vascular variant of CD. Serum levels of interleukin 6 (IL-6) and vascular endothelial growth factor (VEGF) were elevated at 8.9 pg/mL and at 228 pg/mL respectively, but human immunodeficiency virus (HIV) RNA and human herpesvirus 8 (HHV-8) DNA were undetectable. The patient responded well to glucocorticoids (GC) and cyclosporin A. Case 2: A 49-year-old woman had fever, hypertension, anasarca, anemia, thrombocytopenia (50x10 3 /μL) with increased IgG-bound platelets, renal dysfunction, systemic lymphadenopathy, elevated CRP (5.12 mg/dL), hypoalubuminemia and positive LAC, but no autoantibodies detected. Serum IL-6 (6.4 pg/mL) and VEGF (392 pg/mL) were increased and HHV-8 and HIV were negative. CT scan revealed systemic lymphadenopathy, massive fluid retention in the pleural, pericardial and peritoneal cavity and hepatosplenomegaly. Renal biopsy showed mesangioproliferative glomerulonephritis. Further examination showed dry tap bone marrow aspiration and no CD-specific lymph node histological findings. The patient was refractory to GC but was successfully treated with the addition of cyclosporin A. Case 3: A 56-year-old had fever, general fatigue, progressive edema, albuminuria (>0.5g/day), leucopenia (3.45x10 3 /μL), thrombocytopenia (37x10 3 /μL) and anemia. Her serum CRP (18.41 mg/dL), IL-6 (41.6 pg/mL) and VEGF (106 pg/mL) were markedly elevated. RF, ANA and LAC were positive. HHV-8 and HIV were both negative. CT scan indicated multiple low-grade lymphadenopathy, massive pleural and peritoneal effusion and hepatosplenomegaly. In addition to dry tap bone marrow aspiration, lymph node biopsy showed the histology of the hyaline vascular variant of CD. Despite aggressive therapy with high-dose GC and tocilizumab, her systemic fluid retention and inflammation progressed and died of bleeding and multiple organ failure. Serum IL-6 and VEGF increased according to the worsening condition. Conclusions: Patients with TAFRO syndrome show the manifestations and laboratory findings similar to SLE, including fever, systemic lymphadenopathy, anasarca and cavity effusions, thrombocytopenia, and production of autoantibodies, at least in part due to IL-6 overproduction. It may be of interest to determine whether this SLE mimicker, so far unique to Japan, may be distributed in other countries. Disclosure of Interest: None declared